P158 ELECTROANATOMIC MAPPING–GUIDED DEFIBRILLATOR IMPLANTATION WITH CARTO 3 IN YOUNG PATIENTS. (18th May 2022) - Loira, L; Fumanelli, J; Elhyka, A; Rotella, M; Ferretto, S; Di Salvo, G; Iliceto, S
Abstract: Introduction: Defibrillator (ICD) implantation is generally performed under fluoroscopy guidance, allowing to place the leads in the correct positions within the heart. However, for young patients, fluoroscopy exposure should be reduced as much as possible due to their higher radiosensitivity. Three–dimensional (3D) electroanatomical mapping (EAM) is a technique extensively used in electrophysiology for the ablation of different arrythmia, reducing the fluoroscopy exposure. In this preliminary study 3D EAM was used to achieve ICD implantation in pediatric patients and in young patients with congenital heart disease targeting minimal fluoroscopy exposure. Data on procedure complications, fluoroscopy dose and time were compared to those achieved with the conventional approach without 3D EAM. Methods: Using the EAM system CARTO 3 (Biosense Webster, Johnson & Johnson Medical, CA) ICD implantation was performed in 10 young patients: 8 had an age below 18 (mean 13 y ± 2) at the time of the implantation and 2 were adults with congenital heart disease (24 and 38 y). For comparison, 10 pediatric patients (mean 13 y ± 2) and 2 adults with congenital heart disease treated conventionally, without EAM, were considered. In the EAM group, the physician started by mapping the chambers of interest with a sensor–based catheter (Navistar Biosense Webster, Johnson & Johnson Medical, CA). Then the leads were advanced in the heart and visualized on the CARTO 3 system utilizing alligator clips attached to the distal part of each lead and connected to the EAM system. A final fluoroscopic snapshot image was taken to confirm the correct deployment of the leads. Results: The total procedure time was similar between the two groups with a mean time of 61 min in the EAM group and 72 min in the conventional group. The mean fluoroscopic time and dose were lower in the EAM group (22 sec, 6.6 Gy·cm2) compared to the conventional group (887 sec, 39 Gy·cm2). There were no peri–procedural or follow–up complications in either group. Within the EAM group, a decreasing trend is observed in total procedure time, fluoroscopic time and dose by increased number of procedures. Conclusion: Implantation of ICD under EAM guidance in young patients is feasible and allows for reduced fluoroscopic exposure, without compromising safety.